Compressive strength performance of sustainable concrete incorporating rice husk ash and sugarcane bagasse ash as agricultural waste-based supplementary cementitious materials - Arifurrahman; Agil Dwi Cahyadi; Pramudya Kurniawan; Randy Setiawan; Wattini; Qalbi Hafiyyan (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: The growing environmental concerns associated with Portland cement production have encouraged the utilization of agricultural waste as supplementary cementitious materials for sustainable concrete. Rice husk ash (RHA) and sugarcane bagasse ash (SCBA) are silica-rich by-products with pozzolanic potential that can reduce cement consumption while promoting environmentally responsible construction. Aim: This study aimed to evaluate the compressive strength performance of sustainable concrete incorporating RHA and SCBA and to determine the most effective mixture proportion for structural concrete applications. Method: A pure experimental approach was employed using concrete with a target compressive strength of 21 MPa at 28 days. RHA was used as a constant 10% cement replacement by weight, while SCBA was incorporated at 1%, 3%, 5%, 7%, and 9% of the binder content. Superplasticizer was added to maintain workability within a slump range of 6–18 cm, and compressive strength was evaluated after 7, 14, and 28 days of curing. Results: Increasing SCBA content progressively reduced compressive strength because of its porous structure and high water demand, which limited cement hydration. The mixture containing 10% RHA and 1% SCBA exhibited the highest compressive strength among the modified concretes, although it remained below the control concrete (25.51 MPa) and the targeted structural strength. Conclusion: RHA and SCBA have potential as agricultural waste-based supplementary cementitious materials for sustainable concrete, particularly for non-structural applications. Further optimization of ash processing and mixture proportions is required to enhance their mechanical performance and broaden their structural applicability.